Fine wares from the Late Roman ‘Principia’at Capidava (II) - Alexandru Rațiu; Ioan C. Opriș; Mihai Duca (Cercetări Arheologice, 2023)
The Late Roman principia from Capidava was built at the end of the 3rd – beginning of the 4th century, most likely during the general reconstruction (phase II) of the fort, as a result of the bellum Scythicum. The building was fully excavated in successive campaigns between 2013-2019. This paper is a follow-up to an initial article, published in 2017, dealing with the fine pottery finds discovered during the 2013-2014 campaigns. In what follows, we will focus on the same category of finds, resulting from the systematic excavation during the 2016 campaign. The 66 items in our catalogue belong to six different classes: African Red Slip Ware, Late Roman C / Phocean Ware, Pontic Sigillata Ware, Early Pontic Red Slip Ware, Pontic Red Slip Ware and Late Roman Light Colored Ware. Within each class our objects have been divided into several types and sub-types according to the extensive existing bibliography. The high degree of fragmentation of the vessels is also the result of the overlap of the living in the building with the semi-deep dwellings built in the final so-called Middle Byzantine period (9th – 11th centuries).